EVALUATION AND BEHAVIOURAL ASPECTS OF HAND WASHING IN HEALTH CARE PROVIDERS - VINAY KHANNA; KRITI TILAK; RUCHEE KHANNA; CHIRANJAY MUKHOPADHYAY (International Journal of Pharma and Bio Sciences, 2015)
Proper hand hygiene is the single most essential, simplest and economical means of reducing the prevalence of hospital acquired infections and the spread of antimicrobial resistance. The current study was conducted on fifty health care providers (including doctors, respiratory therapists, physiotherapists, nurses and ward boys) who were inquired on their awareness and habit of handwashing. Samples were also collected before and after hand wash using different combinations of plain soap or antiseptic soap with or without alcohol based hand rub. Pre-wash and post-wash samples were cultured on blood agar and bacterial colonies were counted. Data was analysed using SPSS software ver 20.0. It was found that all the health care providers were aware of the benefits and proper technique of handwashing. Median reduction in colony forming units/ml following handwashing was maximum in subjects using plain soap and water and alcohol based hand rub (66.98%) exceeding marginally to those using antiseptic soap and water and alcohol based hand rub (66.15%).Frequency of handwashing>5 times per day was seen mostly in nurses. Median number of colony forming units/ml grown from sample collected from hands of doctors before handwashing was maximum indicating worst hand hygiene. Thus, we conclude that the health care practitioners in our country need to brace themselves to inculcate the simple, basic and effective practice of hand hygiene in their daily patient care activities. Handwashing should become an educational priority, increasing the emphasis on infection control.